OP0187-PC Potentially harmful prescription of NSAIDS in a primary care population with musculoskeletal complaints. (23rd January 2014) - Koffeman, A.; 't Jong, G.; Valkhoff, V.; Warlé-van Herwaarden, M.; Luijsterburg, P.; Sturkenboom, M.; Bierma-Zeinstra, S.; Bindels, P.
Abstract : Background: To reduce adverse drug events (ADEs), clinical guidelines recommend cautious prescription of non-steroidal anti-inflammatory drugs (NSAIDs) in patients known to be at a high risk of developing a serious ADE. General practitioners (GPs) frequently prescribe NSAIDs in the treatment of musculoskeletal complaints (MSC). Objectives: To determine the extent of prescription and of potentially harmful prescription of NSAIDs in a primary care population with MSC. Methods: Data were retrieved from the Integrated Primary Care Information (IPCI) database, a longitudinal GP research database containing over one million patient records1. All new episodes of MSC occurring in adult patients (≥18 years) between 2000 and 2010 were identified based on the International Classification of Primary Care (ICPC)-coding. An episode was considered new if the patient had not consulted their GP for the same complaint in the six months prior to consultation. For all episodes, NSAID prescriptions issued on the day of consultation were subsequently identified. NSAID prescriptions were considered potentially harmful if given to patients at a high risk of adverse events at the time of NSAID prescription, defined as a high renal risk (glomerular filtration rate <30ml/min), high cardiovascular (CV) risk (history of ischaemic heart disease, stroke, peripheral arterial disease or heart failure) or high gastro-intestinal (GI) risk (history of upper GI bleeding or ulceration, age>70 years, or two or more of the following: age 60-70 years, history of heart failure, diabetes or severe rheumatoid arthritis, use of antithrombotics, corticosteroids, selective serotonin reuptake inhibitors or high dose NSAIDs) without adequate concomitant gastroprotection (either a cox-2 selective inhibitor or a non-selective NSAID with concomitant proton pump inhibitor, misoprostol or histamine-2 receptor antagonist). Results: In total, 1, 632, 005 episodes of MSC occurred in 474, 201 adult patients between 2000 and 2010. In 401, 473 (24.6%) of these episodes, concerning 221, 539 (46.7%) of all patients, an NSAID was prescribed. The percentage of NSAID prescriptions decreased over time, from 29.5% in 2000 to 21.2% in 2010 (p<0.001). NSAID prescription rates were highest in episodes of gout (49.9%), shoulder syndrome (41.9%) and non-specific low back pain (38.5%). Of all NSAID-prescriptions, 10.6% were considered potentially harmful to the renal, CV or GI tract. More specifically, 0.03% were prescribed to patients at high renal risk, 6.8% to patients at high CV risk and 8.9% without adequate gastroprotection to patients at high GI risk. When restricting to NSAID's prescribed to patients at high GI risk, adequate gastroprotection was prescribed in only 47.2% of cases. Conclusions: Although prescription rates have decreased significantly over time, GPs still routinely treat MSC with NSAIDs. Patients' risk profiles are not sufficiently taken into account in one tenth of prescriptions, particularly in patients at a high risk of serious gastro-intestinal ADEs. References: Vlug AE, et al. Postmarketing surveillance based on electronic patient records: the IPCI project. Methods Inf Med 1999;38:339-44. Disclosure of Interest: None Declared